Peningkatan Perekonomian Kelompok Ukm Kue Basah Desa Sambirejo Melalui Pemanfataan Energi Alternatif - Margianto, Margianto; Sugiono, Sugiono (University of Islam Malang, 2018)
Sambirejo village have interested potensial among other villages around. The potensial is there are some group of wet cake small businessman. There are 14 small businessman that have many worker among their family.Many years ago the small businessman used LPG (Liquid Petrolium Gas) or woods as source of fire energy to run their working. So that there some negative effect like dangerous of blowing LPG or the emptiness of wood supply. Also they used manual tools to process the wet cake that make unefficently bussiness.The small businessman have many cows and garden that can be used to make biogas installation with use cows manure.Through this campus activity, the businessman at last have biogas installation as fire alternative energy and mechanical tools (mixer cake ) to process their working.Output of the program are, tne small businessman have ability to efficiently and faster the production process